Translation and Validation of Pregnancy Anxiety Instrument into Indonesian: PrAS - Kurniawati, Wiwit; Lantu, Nurlela; Astuti, Yunita Laila; Kusumaningrum, Arie (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: Anxiety is frequently experienced during pregnancy and is recognized as a prevalent psychological issue. The PrAS or stands for Pregnancy-related Anxiety Scale is widely used to measure anxiety specifically associated with pregnancy. Though, it has not yet been validated in Indonesia. Objective: to produce the Indonesian adaptation validity and reliability of the PrAS. Methods: The study's cross-sectional design involved 92 pregnant women recruited from a Community Health Center in Jakarta area. The CVI was utilized to evaluate each item applicability to the concept of pregnancy-related anxiety. Cronbach's Alpha was applied to determine the instrument's internal consistency and inter-item reliability.  Results: The CVI, as assessed by six expert reviewers, yielded values ranging between 0.83 and 1.00, with an average of 0.984. The S-CVI for the PrAS met the recommended threshold of 0.90 or higher. Additionally, the average internal consistency, as measured by Cronbach's alpha, was 0.953..The findings of this pilot study demonstrate that the PrAS is a valid instrument. Conclusions: The Indonesian PrAS adaptation is a reliable and suitable measure for identifying and assessing pregnancy-related anxiety among Indonesian women.